ECONOMIC TENDENCIES, CAPITAL AND INEQUALITIES (Heritage, 2020)
Inequalities in: capital, property, income; the regulations are contemporary and global society. The rate income on capital suprasses rate the economic growth. Implement is enormous concentration  of capital. Large is number a rich mans and extreme wealthy. On other side enormous majority is smaller the well-off and poor. Increase and the layer global plutocrats. Project is decelerate dynamics growth. The futre is foggy uncertainty, as and full risky. Target of the work is perceive growth sociable a inequalities as the urgent contemporary the problem. Apply is various the methodology (historical, deductive-inductive, structural, comparative, statistical and other analysis). The problem it is concentration of capital and possibility reduce the social divide. Similarly swear, the problem is it and long-term the decelerate  dynamics of the economic growth. Conclude is that benefical influence powers of the convergency and (or) of the divergence, as and mixed of the efficiencies whose a resultant to be able in the direction reduce a global inequalities. Development individually a regions to be able and to dynamism of the economis growth. Philospohical and economic, rate the return of capital surpass the rate economic growth (p>g). This the trend anticipate is and in 21. century. „The first basic law of capitalism“:  a participation income of capital in national income (a) increase is rate the return (r) on capital and relation capital and income (b) that is a = r x b. „Other basic law of capitalism“: relation capital and income (b) quotient is rate of saving (s) and rate growth of national income (g) that is b = s/g. „Law cumulative growth“: rather small annual rate the return in long a deadline cause powerful growth, initial, of capital.  „Law behavior“: money and profit are motor activities! Richest the layer make one percentage of people (1%) on highest top of pyramid!  Plutocracy  create of the world politics.
Keywords: Differents, partitions, inequalitis, capital, property, income, wealth, law, cumulative, money, profit, powers, convergency, divergence, regions, growth, development, plutocracy.